3D Biointerfaces: Electron Microscopy for 3D Scaffolds–Cell Biointerface Characterization (Adv. Biosys. 2/2019). Issue 2 (12th February 2019) - Iandolo, Donata; Pennacchio, Fabrizio A.; Mollo, Valentina; Rossi, Domenico; Dannhauser, David; Cui, Bianxiao; Owens, Roisin M.; Santoro, Francesca
Abstract : In article number1800103, Francesca Santoro and co‐workers use a focused ion beam coupled with scanning electron microscopy to acquire high resolution images of cells colonizing polymeric substrates with different geometries. The technique allows for highly detailed images with no damage caused to the substrates and to the cells colonizing them, with no artifacts being created. The intimate contact between the investigated cells and materials with complex geometries can now be revealed with definition.